[(64)Cu]NOTA-pentixather enables high resolution PET imaging of CXCR4 expression in a preclinical lymphoma model - Poschenrieder, Andreas (EJNMMI Radiopharm Chem, 2017)
BACKGROUND: The chemokine receptor 4 (CXCR4) is an important molecular target for both visualization and therapy of tumors. The aim of the present study was the synthesis and preclinical evaluation of a (64)Cu-labeled, CXCR4-targeting peptide for positron emission tomography (PET) imaging of CXCR4 expression in vivo. METHODS: For this purpose, 1,4,7-triazacyclononane,1-glutaric acid-4,7-acetic acid (NODAGA), or 1,4,7-triazacyclononane-triacetic acid (NOTA) was conjugated to the highly affine CXCR4-targeting pentixather scaffold. Affinities were determined using Jurkat T-lymphocytes in competitive binding assays employing [(125)I]FC131 as the radioligand. Internalization and efflux studies of [(64)Cu]NOTA-pentixather were performed in chem-1 cells, stably transfected with hCXCR4. The stability of the tracer was evaluated in vitro and in vivo. Small-animal PET and biodistribution studies at different time points were performed in Daudi lymphoma-bearing severe combined immunodeficiency (SCID) mice. RESULTS: [(64)Cu]NOTA-pentixather was rapidly radiolabeled at 60 °C with high radiochemical yields ≥90% and purities >99%. [(64)Cu]NOTA-pentixather offered the highest affinity of the evaluated peptides in this study (IC(50) = 14.9 ± 2.1 nM), showed efficient CXCR4-targeting in vitro and was stable in blood and urine with high resistance to transchelation in ethylenediaminetetraacetic acid (EDTA) challenge studies. Due to the enhanced lipophilicity of [(64)Cu]NOTA-pentixather (logP = -1.2), biodistribution studies showed some nonspecific accumulation in the liver and intestines. However, tumor accumulation (13.1 ± 1.5% ID/g, 1.5 h p.i.) was CXCR4-specific and higher than in all other organs and resulted in high resolution delineation of Daudi tumors in PET/CT images in vivo. CONCLUSIONS: [(64)Cu]NOTA-pentixather was fast and efficiently radiolabeled, showed effective CXCR4-targeting, high stability in vitro and in vivo and resulted in high resolution PET/CT images accompanied with a suitable biodistribution profile, making [(64)Cu]NOTA-pentixather a promising tracer for future application in humans.